Induction of labour: creation of a classification of Grenoble allowing an assessment of the evaluation of practices - Manon Vanneaux; Pierre-Louis Forey; Véronique Equy; Pascale Hoffmann; Didier Riethmuller (BMC, 2022)
Abstract Background Induction of labour, a very common obstetric procedure, affects about one in five pregnant women in most developed countries. Induction of labour is medically indicated, is subject to risks and additional costs, and is often poorly experienced by patients. The practices concerning induction vary widely from centre to centre and therefore need to be evaluated. Our aim was to develop a tool for evaluating induction of labour which would facilitate geographical and temporal comparisons. Methods We have created a classification based on the principles of the internationally known Robson classification. It should be simple, robust, reproducible and require readily available data in each file. The groups are fully inclusive and mutually exclusive. This classification has been validated by a Delphi method. Results Our classification includes 8 clinically relevant groups according to 5 obstetrical criteria. In order to classify each patient into a group, a simple system based on a maximum of 7 successive questions (from 1 to 7 questions) is used. Our classification has been validated by 13 national experts with satisfactory overall approval. Conclusions With a view to improving the quality of care, our Grenoble classification would allow a standardization of the evaluation of practices of the induction of labour over time in the same maternity hospital. It would also allow the comparison of practices within different maternity hospitals in a network, a country or even different countries.